Intravenous injection of indocyanine green to enhance laser‐assisted coagulation of blood vessels in skin – an animal study. (7th June 2012) - Bäumler, W.; Paasch, U.; Klein, A.; Landthaler, M.; Friedman, R.; Shafirstein, G.
Abstract: Background  Laser therapy of vascular lesions, such as port wine stains (PWS) or leg veins are still imperfect due to different diameters and depth of vessels in tissue. We propose to improve blood vessel coagulation by intravenous introduction of an exogenous chromophore (indocyanine green, ICG) that effectively converts near‐infrared (NIR) laser light into heat. Objective  The purpose of this study was to determine the plasma clearance rate, systemic toxicity and histological effects of ICG‐assisted laser therapy in an animal model. Methods  Piglets received intravenous injection of ICG. Blood samples were collected at different times. Systemic toxicity was assessed by measuring liver enzyme levels and other indicators of liver function. The plasma clearance rate of ICG was determined by light absorption measurement in blood samples. The skin was irradiated with a diode laser (810 nm) using radiant exposures from 31 to 80 J/cm². Skin reaction at the treatment site was graded, and punch biopsies were taken for histological examination at 24 and 72 h after treatment. Results  No hepatic toxicity was observed. The clinical examination revealed no adverse skin reactions at 24 or 72 h after laser irradiation. This was confirmed by histological evaluation that showed efficient vessel coagulation without damage of the epidermis or dermis. Conclusions  In light of these in vivo results, we suggest that ICG‐assisted laser therapy could substantially improve clinical outcomes of PWS or leg veins treatment with minimal risk of adverse reactions.